Hepatitis B, Hepatitis C and HIV in the Irish prisoner population : an overview of prevalence rates and risk factors - Long, Jean, 1961- (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2002)
Introduction: This thesis reports the estimated prevalence of antibodies to hepatitis B core antigen, hepatitis C virus and HIV in two distinct prison populations. -- Objective: This thesis provides a synthesised analysis of the prevalence of blood borne viral infections and their determinants in the Irish prisoner population, both entrants (committal) and inmates (census).
Keywords: Medicine, Ph.D.; Ph.D. Trinity College Dublin